2014
DOI: 10.1177/1356766713502485
|View full text |Cite
|
Sign up to set email alerts
|

Examining the moderating role of rational-versus emotional-focused websites

Abstract: This paper examines whether emotional or rational advertising appeals are more effective for website hospitality services. Specifically, it considers how attitudes towards websites, service expectations and attitudes towards boutique hotels may influence the two different types of advertising appeals and purchase intention. Results show that websites using emotional appeals tend to show a positive relationship between attitude towards hotels and attitude towards websites and purchase intention. It also indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 98 publications
(178 reference statements)
3
26
0
1
Order By: Relevance
“…Rational appeal failure in influencing memory and attitude proves that emotional content, especially on video-based e-commerce advertising, is more effective. This result is in line with the findings of other studies that compare effectiveness of these both advertisement appeals (Heath & Nairn, 2005;Park, 2012;Lwin et al, 2014). This shows that consumers tend to use emotion in deciding whether to buy a product or use a service.…”
Section: Discussionsupporting
confidence: 82%
“…Rational appeal failure in influencing memory and attitude proves that emotional content, especially on video-based e-commerce advertising, is more effective. This result is in line with the findings of other studies that compare effectiveness of these both advertisement appeals (Heath & Nairn, 2005;Park, 2012;Lwin et al, 2014). This shows that consumers tend to use emotion in deciding whether to buy a product or use a service.…”
Section: Discussionsupporting
confidence: 82%
“…Previous research on "boutique accommodations" revealed its potential to increase the experiential nature of heritage since it can capitalize on the unique and original character of the property, augment the homely feel and pattern its catering services after the nature and heritage cuisines of its physical location (Chang & Teo, 2008;McIntosh & Siggs, 2005;Rogerson, 2010;Yuan, 2009). Similarly, research on boutique hotels has suggested that the design aspects of converted heritage hotels, such as gardens, great halls, iconic architecture, personalized decoration and sense of localism, could inspire the customers' distinctive experience, and further positively affect their attitude toward the destination (Aggett, 2007;Freund de Klumbis & Munsters, 2005;Kleinrichert, Ergul, Johnson, & Uydaci, 2012;Lwin, Phau, Huang, & Lim, 2014;McIntosh & Siggs, 2005;Sklair, 2010). Furthermore, luxurious heritage hotels, especially those converted from old palaces, may retain some superior material objects such as custom-made chandeliers, rare antique furniture, grand marble staircases, priceless statues, stained-glass windows and objects d'art, which have potential to amplify the tourist experience (Mendiratta, 2013).…”
Section: Please Scroll Down For Articlementioning
confidence: 98%
“…His study also demonstrates that positive emotions influence environment attitudes more significantly. Lwin et al (2014) verified which type of appeal (rational or emotional) is more effective when inserted in publicity of hospitality services on websites. Results indicated that the websites with emotional appeal create a more positive relation with the consumer's attitude and intention of purchase.…”
Section: Rational and Hedonic Communication With And Without Sustainamentioning
confidence: 96%